(untitled) (Italian Journal of Public Health, 2005)
Background. The genetic relationship among different species within the genus Proteus has still not been clarified and previous studies by rRNA gene restriction patterns (ribotypes) suggested a high genetic variability in the presently recognised nomenspecies. Methods. The usefulness of rpoB sequencing for inter- and intraspecies discrimination in the genus Proteus was evaluated on 11 type and clinical strains belonging to the four described species: P. penneri, P. vulgaris, P. mirabilis, and P. myxofaciens. Results. The rpoB sequencing proved able to characterise the different species, showing six well defined rpoB sequence groups in the 1153 bp region analysed. P. myxofaciens and P. mirabilis could be clearly differentiated from the types and clinical strains of the other species showing sequence divergences of 19.5- 23% and 6.6-7.6%, respectively. Two groups of P. vulgaris sequences could be described, one of them including the new strain type, differing from each other by 3.3-3.6% of their nucleotides (nt) and for both of them 6.5-6.8% nt differences from the stand-alone former P. vulgaris strain type were found. P. penneri differed by only 2.3-3% from all P. vulgaris strains, however, differed from the former P. vulgaris strain type by 5.5-5.8%. Conclusions. Our results confirm previous ribotyping data regarding the validity of the presently recognised nomenspecies within the genus Proteus, but provides further evidence for the existence of genetic differences within the P. vulgaris species.